A Systematic Literature Review of Hydrodynamic and Sedimentation Modelling: Research Trends and Methods - Anita Fitriani; Hendra Achiari (Syntax Idea)
This study aims to identify and analyse the trends and patterns of hydrodynamic and sedimentation modeling research from 2013 to 2022. A systematic literature review was conducted on publications from various databases, resulting in 39 relevant papers. The results show that the topic of hydrodynamic and sedimentation modeling has been increasing in popularity, with geomorphology as the most frequently published journal. Most studies focus on natural environmental interactions with current and sediment patterns using the Delft3D modeling software. The validation of the model is performed by comparing the observed current velocity results. Coupled models were used in only 44% of the reviewed literature. Overall, the findings suggest a significant gap in hydrodynamic and sedimentation modeling research, and more research is needed to address this issue.